Climate change impacts on food security and nutrition of India: Foresight analysis - Nedumaran. S.; Padmanabhan, Jyosthnaa; Kumar, Shalander; Das, Abhishek; Paithankar, Pradnya; Kumar, Abhay; Jain, Ayushi; Avinandan, Vijay (World Food Programme, 2023)
Agriculture is a significant and primary sector of the Indian economy and is crucial for ensuring the food, nutrition, and livelihood security of about 80% of the population. Even though India has achieved ‘selfsufficiency’ in food grains production through Green Revolution, it faces challenges like loss of soil fertility, waterlogging, ground, and surface water pollution, intensified pests and diseases, increased farm input prices, and regional disparity (Cummings, 2019). In addition, climate change has added a new dimension to the existing problems by posing a significant threat to Indian agriculture in general and food and nutrition security in particular.